Xanthan gum protects rabbit articular chondrocytes against sodium nitroprusside-induced apoptosis in vitro. (20th October 2015) - Chen, Qixin; Mei, Xifan; Han, Guanying; Ling, Peixue; Guo, Bin; Guo, Yuewei; Shao, Huarong; Wang, Guan; Cui, Zan; Bai, Yuxin; Xu, Fang
Highlights: Xanthan gum reversed SNP-reduced rabbit chondrocytes proliferation. Xanthan gum declined early apoptosis rate and maintained the morphology of SNP-induced rabbit chondrocytes. Xanthan gum alleviated SNP-induced rabbit chondrocytes loss/disruption of mitochondrial membrane potential. Xanthan gum down-regulated the levels of PGE2 in SNP-induced rabbit chondrocytes in medium. Abstract: We have previously reported that intra-articular injection of xanthan gum (XG) could significantly ameliorate the degree of joint cartilage degradation and pain in experimental osteoarthritis (OA) model in vivo . In this present study, we evaluated the protective effect of XG against Sodium nitroprusside (SNP)-induced rabbit articular chondrocytes apoptosis in vitro . Rabbit articular chondrocytes were incubated with various concentrations of XG for 24 h prior to 0.5 mmol/L SNP co-treatment for 24 h. The proliferation of chondrocytes was analyzed using MTT assay. The chondrocytes early apoptosis rates were evaluated using Annexin V-FITC/PI flow cytometry. The morphology of apoptosis chondrocytes were observed by scanning electron microscopy (SEM). The loss/disruption of mitochondrial membrane potential was detected using rhodamin 123 by confocal microscope. The concentration of prostaglandin E2 (PGE2 ) in cell culture supernatants was evaluated using ELISA assay. The results showed that XG could significantly reverse SNP-reduced cell proliferation and inhibited cell early apoptosis rate in a dose-dependent manner. XG alleviated loss/disruption of mitochondrial membrane potential and decreased the PGE2 level of chondrocytes cell culture supernatants in SNP-induced chondrocytes. These results of the present research strongly suggest that XG can protect rabbit articular chondrocytes against SNP-induced apoptosis in vitro .